2004
DOI: 10.1002/jcb.20198
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency electromagnetic fields as effectors of cellular responses in vitro: Possible immune cell activation

Abstract: There is presently an intense discussion if electromagnetic field (EMF) exposure has consequences for human health. This include exposure to structures and appliances that emit in the extremely low frequency (ELF) range of the electromagnetic spectrum, as well as emission coming from communication devices using the radiofrequency part of the spectrum. Biological effects of such exposures have been noted frequently, although the implication for specific health effects is not that clear. The basic interaction me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
141
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(161 citation statements)
references
References 75 publications
7
141
0
7
Order By: Relevance
“…El análisis comparativo del insomnio por barrio evidenció una mayor proporción de personas que duermen mal en el barrio Nogales, en el cual hay muchas antenas de radio y telefonía móvil, que la encontrada en el barrio Modelo, expuesto en mucha menor medida (p<0,05), lo que sugiere la posible influencia de una mayor carga de campos magnéticos proveniente de esta fuente y coincide con la teoría que proclama la acción supresora de la producción de la hormona melatonina durante la noche, mediada por el incremento en los radicales libres, debida a la exposición crónica a dichos campos (18). Este hallazgo concuerda con lo reportado en otros estudios recientes de similar diseño en Alemania (19) e Irán (20), aunque en ellos la distancia entre la vivienda y las estaciones de telefonía móvil fue reportada por los propios participantes.…”
Section: Discussionunclassified
“…El análisis comparativo del insomnio por barrio evidenció una mayor proporción de personas que duermen mal en el barrio Nogales, en el cual hay muchas antenas de radio y telefonía móvil, que la encontrada en el barrio Modelo, expuesto en mucha menor medida (p<0,05), lo que sugiere la posible influencia de una mayor carga de campos magnéticos proveniente de esta fuente y coincide con la teoría que proclama la acción supresora de la producción de la hormona melatonina durante la noche, mediada por el incremento en los radicales libres, debida a la exposición crónica a dichos campos (18). Este hallazgo concuerda con lo reportado en otros estudios recientes de similar diseño en Alemania (19) e Irán (20), aunque en ellos la distancia entre la vivienda y las estaciones de telefonía móvil fue reportada por los propios participantes.…”
Section: Discussionunclassified
“…27 Some people who are electrically hypersensitive complain of pain or pressure in the chest area, heart palpitations, and/or an irregular heartbeat, accompanied by feelings of anxiety that develop rapidly. The symptoms resemble a heart attack and thus contribute to even more anxiety.…”
Section: -26mentioning
confidence: 99%
“…Recent studies in Behavioral and psychological fields have shown that exposure to electromagnetic fields (EMFs) can change human cognitive functions and behaviors of animals [1,2]. For instance it is reported that neither short term (7 days), Nor long term exposure to 25-50Hz fields did not make a change in motor activity, but 50 Hz field exposure will decrease recognition of new arm of the Y maze [3].…”
Section: Introductionmentioning
confidence: 99%